Answer:
![x = (5)/(3) , \ \ y = -1](https://img.qammunity.org/2022/formulas/mathematics/high-school/peauu485ekskgdymmisg0tqsg0a2bq487p.png)
Explanation:
6x + 5y = 5 -----(1)
9x - 4y = 19 -----(2)
Multiply (1) by 9 : 54x + 45y = 45 ------(3)
Multiply (2) by 6 : 54x - 24y = 114 -------(4)
(3) - (4) ==> 69y = -69
y = -1
Substitute y = -1 in (1)
6x + 5(-1) = 5
6x - 5 = 5
6x = 5 + 5
6x = 10
![x =(10)/(6) = (5)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ify2q4gt4zrresrtb5a5qlsvco9jguxuhe.png)